2017
DOI: 10.21873/invivo.11088
|View full text |Cite
|
Sign up to set email alerts
|

Safety Evaluation of Trastuzumab Emtansine in Japanese Patients with HER2-Positive Advanced Breast Cancer

Abstract: Abstract. Background/Aim: Tolerability and safety of trastuzumab emtansine (T-DM1) was investigated inThe human epidermal growth factor receptor 2 (HER2) has been shown to play an important role in the development and progression of certain types of breast cancer. HER2 is overexpressed in ~20% of patients with breast cancer and is associated with a more aggressive tumor growth and poor clinical outcome (1-3). Since trastuzumab, an anti-HER2 humanized monoclonal antibody, demonstrated the significant survival b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In recent years, with the research and development of tumor molecular biology, it has been found that the positive expression of the HER2 receptor is associated with the poor prognosis of GC [3] . It is considered a new biomarker diagnostic factor and the preferred target for cancer therapy, bringing tumor treatment into a new era [13] , [14] , [15] , [16] . Inhibiting HER2 activity with monoclonal antibodies, ADC, or small molecular kinase inhibitors are common methods for the treatment of HER2-positive GC.…”
Section: Her2-low Expressing Gastric Cancermentioning
confidence: 99%
“…In recent years, with the research and development of tumor molecular biology, it has been found that the positive expression of the HER2 receptor is associated with the poor prognosis of GC [3] . It is considered a new biomarker diagnostic factor and the preferred target for cancer therapy, bringing tumor treatment into a new era [13] , [14] , [15] , [16] . Inhibiting HER2 activity with monoclonal antibodies, ADC, or small molecular kinase inhibitors are common methods for the treatment of HER2-positive GC.…”
Section: Her2-low Expressing Gastric Cancermentioning
confidence: 99%
“…Additionally, the incidence of IRs in Japanese patients who had received the trastuzumab emtansine was 1.7% (4/232) and much lower in this study (6). The difference could be explained by the fact that patients with previous treatment of trastuzumab and without severe IRs due to trastuzumab were included in the previous study.…”
Section: Discussionmentioning
confidence: 55%
“…Of the 37 trials included in the systematic review, 13 were randomized controlled trials (RCTs) 11 , 12 , 14 , 15 , 18 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 and 24 were single-arm clinical trials. 13 , 16 , 17 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 The HER2-targeted ADCs used in eligible studies included T-DM1 (n = 25) and T-DXd (n = 14). The studies involved the treatment of breast cancer (n = 28), lung cancer (n = 4), gastric cancer (n = 4), colorectal cancer (n = 1), and mixed cancer types (n = 2).…”
Section: Resultsmentioning
confidence: 99%